2010
DOI: 10.1161/hypertensionaha.110.156273
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaldosteronism and Left Ventricular Hypertrophy

Abstract: In their prospective study, Gaddam et al 1 have examined the effects of spironolactone on cardiac structure in 34 patients with resistant hypertension who were separated according to their plasma aldosterone levels. At baseline, cardiac volume overload was detected in patients with higher aldosterone levels that was significantly and rapidly reduced by spironolactone, whereas left ventricular (LV) mass was comparable at baseline and decreased significantly after treatment in both patients with higher and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Knowledge of the effects of aldosterone and its antagonists on LV mass is important, because hypertrophy is an important predictor of major cardiovascular events. These effects might be relevant not only in patients with primary aldosteronism, but also in patients with lesser degrees of aldosterone excess . Finally, there is evidence from studies with spironolactone that aldosterone‐related mechanisms could be involved in atrial fibrillation and flutter, as well as in ventricular arrhythmias .…”
Section: Aldosterone and The Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the effects of aldosterone and its antagonists on LV mass is important, because hypertrophy is an important predictor of major cardiovascular events. These effects might be relevant not only in patients with primary aldosteronism, but also in patients with lesser degrees of aldosterone excess . Finally, there is evidence from studies with spironolactone that aldosterone‐related mechanisms could be involved in atrial fibrillation and flutter, as well as in ventricular arrhythmias .…”
Section: Aldosterone and The Cardiovascular Systemmentioning
confidence: 99%
“…These effects might be relevant not only in patients with primary aldosteronism, but also in patients with lesser degrees of aldosterone excess. 36 Finally, there is evidence from studies with spironolactone that aldosterone-related mechanisms could be involved in atrial fibrillation and flutter, 37,38 as well as in ventricular arrhythmias. 39 This evidence suggests that mineralocorticoid receptor blockers might be seen as a choice for the prevention of both supraventricular and ventricular arrhythmias, an issue that needs to be further investigated in appropriately designed trials.…”
Section: Aldosterone and The Cardiovascular Systemmentioning
confidence: 99%
“…Knowledge of the eff ects of mineralocorticoid receptor antagonists on LV mass is important because LV hypertrophy is an important predictor of major cardiovascular events. These benefi ts could be relevant not only in patients with primary aldosteronism, but also in patients with lesser degrees of aldosterone excess [ 48 ] and this hypothesis will have to be tested in future studies.…”
Section: Essential Hypertension ▼mentioning
confidence: 99%
“…Essential Hypertension ▼ Similar to PA, significant contribution of plasma aldosterone levels to LV mass has been reported in some studies conducted in patients with EH, suggesting that this contribution might be relevant also in the presence of lesser degree of aldosterone excess [31]. Cross-sectional studies have reported a direct relationship between plasma aldosterone and LV mass [32], a relationship that was stronger in EH patients of Afro-Caribbean descent [33], with the metabolic syndrome [34], or activated hemostatic and hemorheological factors [35].…”
mentioning
confidence: 88%